Analysis The Quality of Services For Krl Jabodetabek Bekasi Jakarta City Line Based on The User's Point of View During The Covid-19 Pandemic - Muhammad Luay Ghozy Rizq (International Journal of Social Service and Research, 2021)
KRL Commuter Line is one of the dominant modes of public transportation used by the public in the Jabodetabek area, including commuting from the Bekasi area to Jakarta and vice versa. The KRL Jabodetabek Bekasi-Jakarta city line is one of the busiest KRL lines. This study aims to describe the usability aspects as well as the convenience and comfort aspects in order to evaluate the quality of the KRL commuter line based on the user's point of view. This study uses quantitative methods and descriptive analysis. The results showed that during the Covid-19 pandemic, the quality of service level of the KRL Jabodetabek Bekasi-Jakarta city line was quite adequate category. Therefore, it can be concluded that the majority of users consider that the aspects of availability and aspects of convenience and comfort are adequate in the services of KRL Jabodetabek Bekasi Jakarta city line